Design-based research for the development of augmented reality applications: the case of virtual playground - Manoela Milena Oliveira da Silva; João Barbosa Moizes; Patricia Smith Cavalcante; Veronica Teichrieb (Em Teia)
Augmented Reality applications for education change the classroom experience for both teachers and students. However, the use of these tools is not widespread yet. Current applications still have some limitations, such as: hard to use interfaces, lack of freedom to create content, lack of support for a shared experience among others. This work presents the update of Virtual Playground, an application collaboratively created with language teachers, designers and engineers; and Virtual Playground Creator, an authorship tool for this application. This process was developed following Design-based research methodology in two cycles of ideation, implementation and testing. We present the updates and results regarding the second round of six tests of Virtual Playground with teachers. The main goals were to evaluate if Virtual Playground Creator allows teachers to create AR experiences to use in classrooms; and (2) investigate if there were missing or unnecessary features in Virtual Playground Creator. Results have shown that the tool allowed teachers to work with diverse skills and competences. The Virtual Playground Creator prototype allowed the teacher to create their AR experiences proposed, although, in some cases modifications were needed. The main issues were related to the limited 3D library in the prototype evaluated and lack of creation possibilities.